The Strength of Lecturer Interpersonal Communication in The Image Formation of Marketing Communication Students, Bina Nusantara University - Dina Sekar Vusparatih (Humaniora, 2016)
The good relations would have a direct impact on the impression created in the students’ perception. The existence of a positive image of the lecturers would certainly go hand in hand with the creation of a positive image for the majors and the university eventually. This article used case study with qualitative method. The interview was the main tool of data collection. Researchers chosea few students who are still studying during the research but have been studying for few years (3 years or 6 semesters) as the resources/interviewee. It finds that indirectly style and interpersonal communication skills of lecturers can affect image formation majors and university.